From teacher to teacher leader - Reinders, Hayo (Cambridge professional learning, 2023)
Hayo Reinders' book is for teachers who would like to develop the mindset of a teacher leader, and with it, the potential to have a major impact on their teaching community. The book supports teachers in their professional development, through discussion of new concepts and ideas, case studies drawing on the experience of teachers from around the world, and through personal reflection and application to their practice. In short, it supports teachers in identifying teacher leadership skills and implementing them in their context